2018
DOI: 10.2174/1389201019666180829152314
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of 68Ga-DOTA-NT-20.3 Uptake in Pancreatic Adenocarcinoma AsPC-1 Cell Line – in vitro Study

Abstract: Background Neurotensin receptors are overexpressed in several cancer types including pancreatic ductal adenocarcinoma. Three NTR subtypes have been cloned: NTR-1, NTR-2 and NTR-3. The most expressed NTR-1 is not present in normal pancreatic tissue and has a low expression in chronic pancreatitis. Objective Objective of this study was to test in vitro affinity of the new 68Ga labelled neurotensin analogue DOTA-NT-20.3 (fragment 6-13, Ac-Lys(DOTA)-Pro-Arg(N-CH3)-Arg-Pro-Tyr-Tle-Leu) on the human pancreatic ducta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A series of bimodal agents was synthesized (Scheme ). Their structure derives from the sequence of the well-validated peptide agonist NT-20.3 (Ac-Lys-Pro-N-Me-Arg-Arg-Pro-Tyr-Tle-Leu-OH). , A lysine residue was introduced at the N-terminal end of the peptide to conjugate the radiometal chelator and the fluorophore, and different spacers were inserted before the lysine: no spacer, a PEG 2 analogue (8-amino-3,6-dioxaoctanoic acid, or AEEAc), or a PEG 4 chain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of bimodal agents was synthesized (Scheme ). Their structure derives from the sequence of the well-validated peptide agonist NT-20.3 (Ac-Lys-Pro-N-Me-Arg-Arg-Pro-Tyr-Tle-Leu-OH). , A lysine residue was introduced at the N-terminal end of the peptide to conjugate the radiometal chelator and the fluorophore, and different spacers were inserted before the lysine: no spacer, a PEG 2 analogue (8-amino-3,6-dioxaoctanoic acid, or AEEAc), or a PEG 4 chain.…”
Section: Resultsmentioning
confidence: 99%
“…Their structure derives from the sequence of the well-validated peptide agonist NT-20.3 (Ac-Lys-Pro-N-Me-Arg-Arg-Pro-Tyr-Tle-Leu-OH). [21][22][23]26 A lysine residue was introduced at the N-terminal end of the peptide to conjugate the radiometal chelator and the fluorophore, and different spacers were inserted before the lysine: no spacer, a PEG 2 analogue (8-amino-3,6-dioxaoctanoic acid, or AEEAc), or a PEG 4 chain. For the PET modality, we chose to use 68 Ga among other positron-emitting radioisotopes because its short physical halflife matches well with the rapid pharmacokinetics of peptides, and it provides safer dosimetry for the patients compared to 64 Cu.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…82 Neurotensin (NT) is the endogenous ligand of NTR1 and NT-20.3 is an NT(6−13) analogue, showed an excellent affinity for NTR1. 83 After demonstrating binding affinity to cell lines, 84 preclinical researches showed that NT-20.3-based probes were excellent candidates for imaging and therapy of NTR-1-positive PDAC models. 85 Building on previous success, a recent small trial performed by Hodolic et al on three patients with PDAC showed that 68 Ga-NT-20.3 was safe and well tolerated.…”
Section: Neurotensin Receptormentioning
confidence: 99%
“…In pancreatic adenocarcinoma cells, there is an overexpression of neurotensin receptors, which can be targeted with radiolabelled neurotensin analogs (21). In vitro studies showed a high affinity of the 68 Ga-labeled neurotensin analog ( 68 Ga-DOTA-NT-20.3) for the human pancreatic ductal adenocarcinoma cell line AsPC-1 (22).…”
Section: Targeting Neurotensin Receptors In Pancreatic Adenocarcinomamentioning
confidence: 99%